Nepal Paediatric Society Guideline for use of Antibiotics in Critically ill Children in the Pediatric Intensive Care Unit - Shrestha, Dhruba; Amatya, Puja; Sharma, Arun; Shrestha, Shrijana; Sharma, Yograj; Pathak, Santosh; Pokharel, Prakash Jyoti; Shrestha, Nipun; Pokhrel, Santosh; Dongol, Srijana; Raya, Ganendra Bhakta; Ghimire, Amrit; et al. (Journal of Nepal Paediatric Society, 2021)
Justification: Overuse and administration of unnecessary and inappropriate antibiotics are the leading causes for the increased antimicrobial resistance worldwide. Judicious use of antimicrobials can prevent this phenomenon. Objective: Create a collaborative outline for the use of antibiotics in the paediatric intensive care unit for various infections, based on evidence, taking into consideration local antimicrobial susceptibility patterns. Process / Methods: Under the aegis of Nepal Paediatric Society, this guideline has been developed after several meetings of paediatricians working in various hospitals in different parts of Nepal, looking into the prevalent diseases and local sensitivity patterns of antibiotics. Recommendations: This guideline will help standardize the treatment protocol in paediatric intensive care units in Nepal and help paediatricians decide the appropriate use of antibiotics promptly while managing critically ill children. Keywords: Antibiotics; antibiotic sensitivity; antimicrobial resistance; critically ill child; Paediatric Intensive Care Unit